2019
DOI: 10.1002/biof.1580
|View full text |Cite
|
Sign up to set email alerts
|

Lyso‐diacylglyceryltrimethylhomoserine (lyso‐DGTS) isolated from Nannochloropsis microalgae improves high‐density lipoprotein (HDL) functions

Abstract: Many population studies have shown that blood concentrations of high-density lipoprotein (HDL) cholesterol are inversely correlated with risk of cardiovascular disease (CVD). However, in recent studies, increasing blood HDL cholesterol concentrations failed to reduce CVD events. On the other hand, studies suggest that improving HDL quality can be a more efficient tool for assessing atherosclerotic risk than simply measuring blood HDL cholesterol concentration. Thus, improving HDL activity using natural substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Here, we observed a significant increase in betaine-lipid LDGTS content, consistent with a prior Nannochloropsis study, in which ethanol-based lipid extraction achieved the highest LDGTS content [ 36 ]. LDGTS extracts can increase paraoxonase 1 (PON1) activity, thereby protecting macrophages and low-density lipoprotein, and possibly improving high-density lipoprotein and anti-atherogenic function [ 37 ]. In summary, our combined enzyme treatment with ethanol effectively extracted LDGTS from Nannochloropsis lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we observed a significant increase in betaine-lipid LDGTS content, consistent with a prior Nannochloropsis study, in which ethanol-based lipid extraction achieved the highest LDGTS content [ 36 ]. LDGTS extracts can increase paraoxonase 1 (PON1) activity, thereby protecting macrophages and low-density lipoprotein, and possibly improving high-density lipoprotein and anti-atherogenic function [ 37 ]. In summary, our combined enzyme treatment with ethanol effectively extracted LDGTS from Nannochloropsis lipids.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesized and purchased lyso-DGTS derivatives and analogs (final concentration 10 and 20 µg/mL) were incubated with rePON1 for 2 and 4 h at 37 °C in Tris buffer pH 8.4 containing 1 mM CaCl 2 . These concentrations were chosen in accordance with our previous published studies which showed that, in these concentrations, lyso-DGTS has a positive effect on PON1 and HDL activities in vitro and in vivo without inducing a cytotoxic response [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The assay was performed as previously published in our studies [ 25 , 26 ]. Briefly, in 200 μL Tris buffer in a black 96-well plate, 2 μL of bioactive lipid (in DMSO) at various final concentrations (1, 5, 10, 25, 50, 75, and 100 μg/mL) and rePON1 (final concentration 50 µg/mL) were incubated at 37 °C or 25 °C for 4 h; then, fluorescence measurements were performed in a plate reader (Tecan Infinite 200 PRO).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-density lipoprotein (HDL) particles play a major role in preventing atherosclerosis development because of their anti-atherosclerotic properties-collecting excess cholesterol and returning it to the liver, exhibiting antioxidant and anti-inflammatory properties, and improving endothelial cell function [6,10,11]. Paraoxonase 1 (PON1) is a glycoprotein enzyme that is synthesized in the liver and transferred to the bloodstream, where it binds to the HDL particles and confers many of their anti-atherosclerotic properties [12,13].…”
Section: Introductionmentioning
confidence: 99%